Impact of the COVID-19 Pandemic on the Food Industry in the Slovak Republic - Ivana KRAVČÁKOVÁ VOZÁROVÁ; Mariana DUBRAVSKÁ (Communications of International Proceedings, 2021)
The food industry is a very important sector in the industrial portfolio and economy of Slovakia and represents a strategic industry that ensures the food sovereignty of country. The COVID-19 pandemic has affected every sector of the economy. The shock caused by the pandemic is an important test of the resilience of the economics of the Slovak Republic and its food industry not excluding. The goal of this paper is to identify the impact of COVID-19 pandemic on the food industry in the Slovak Republic. The pandemic situation caused a decrease in employment in all mnitored period. In the case revenues, there was a decrease in sales especially in the last months of 2020 compared to the same period of 2019. This decrease continued during the first quarter of 2021. However, it was still not as significant as in other industries, what is mainly due to the essential nature of the production. It is too early to predict whether measures taken, proposals and solutions will allow Slovak food industry to recover most of the consequences of the pandemic, or whether the consequences will be so drastic that they will continue to hamper the economy in the next years.
Keywords: Food Industry. COVID-19 Pandemic. Production. Prices. Employment. Slovak Republic.